2020
DOI: 10.3390/ijms21051819
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Global Epigenetic Modification, Which Determines the Phenotype of Transgenic Rice?

Abstract: Transgenic technologies have been applied to a wide range of biological research. However, information on the potential epigenetic effects of transgenic technology is still lacking. Here, we show that the transgenic process can simultaneously induce both genetic and epigenetic changes in rice. We analyzed genetic, epigenetic, and phenotypic changes in plants subjected to tissue culture regeneration, using transgenic lines expressing the same coding sequence from two different promoters in transgenic lines of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…Interestingly, it has been shown that Agrobacterium -mediated rice transgenic plants carried more unintended genomic mutations compared to particle bombardment or electroporation methods ( Labra et al, 2001 ; Wilson et al, 2006 ). More recently, Fan et al (2020b) reported the tissue culture process possibly causes epigenetic alterations in the rice genome. However, the stability of the epigenetic alterations may differ depending on the genetic background and may potentially be suppressed after some generations ( Fan et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been shown that Agrobacterium -mediated rice transgenic plants carried more unintended genomic mutations compared to particle bombardment or electroporation methods ( Labra et al, 2001 ; Wilson et al, 2006 ). More recently, Fan et al (2020b) reported the tissue culture process possibly causes epigenetic alterations in the rice genome. However, the stability of the epigenetic alterations may differ depending on the genetic background and may potentially be suppressed after some generations ( Fan et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Fan et al (2020b) reported the tissue culture process possibly causes epigenetic alterations in the rice genome. However, the stability of the epigenetic alterations may differ depending on the genetic background and may potentially be suppressed after some generations ( Fan et al, 2020b ). Those genomic alterations are heritable and independently segregate from GOI, which means it is possible that null segregants and GOI lines could carry different genomic profiles apart from the GOI.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that the LPSN could influence the growth of OsNAR2.1 overexpression line, we also grown overexpression OsNAR2.1 line (Ov199) and OsNAR2.1 RNAi knock-down line (RNAi) of Nippobare background with wild type (NP) [ 25 , 26 ] with difference seed N content in four different N content field. The results showed that the plant height, grain yield, total N content of seeds and total N content of plant significantly decrease 22.3, 33, 50 and 38%, respectively, in Ov199-LN compared with Ov199-HN in HN field (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen-deficiency stress can induce heritable alteration in DNA methylation [ 19 ]. Fan et al (2020) reported that overexpression of OsNAR2.1 does change rice DNA methylation status [ 25 ]. However, the research progress regarding epigenetic influence by the nutrient in both external and endogenous seed is very sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al identified that the OsEWL4 gene was a regulator of tiller number and plant biomass (yield of above-ground parts in rice plants) by using targeted mutations of eight rice FLW genes using the CRISPR/Cas9 system [ 11 ]. Fan et al produced overexpression and knockdown transformants of the OsNAR2.1 gene and revealed that changing expression levels of the OsNAR2.1 gene altered global methylation at the whole genome level and the phenotypes of plant height and grain yield at the plant level [ 12 ]. These novel technologies are powerful tools to understand the molecular basis of increasing rice yields.…”
mentioning
confidence: 99%